Study of mechanical and thermal properties for epoxy grouts subjected to seawater conditioning at elevated temperature: tensile test and compressive test - Meor Iqram Meor Ahmad,; Muhammad Afhnan Ahmad Temizi,; Muhammad Yunus Ahmad Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pipelines and risers are major transportation of oil and gas. These components are often exposed to extreme marine environmental conditions that can cause pipelines to fail due to corrosion. Hence, epoxy grouts are used as a coating material on the surface of pipelines and risers for supporting the pipe structure and corrosion prevention. In this case, the efficiency of epoxy grout is important in pipeline rehabilitation. Research on the adaptation of seawater, temperature, and epoxy grouts is carried out to determine the changes in mechanical and thermal properties of the material. The preparation of epoxy grouts was prepared with a mixture of epoxy resins, epoxy hardeners, and aggregates. After the sample compounds have been flattened, the mixture will be put into the mold. The seawater aging process was performed for seven days before conducting laboratory experiments. After the seawater aging process, there were physical changes on the surface of the epoxy grouts which are the epoxy grout become harder and there were voids that can act as stress concentration points that may cause micro-crack on the specimen. Next, tensile (ASTM 638) experiments were performed at different temperatures of 27°C, 40°C, 52°C, 72°C, 80°C and 100°C while the result of compression experiment is based on the literature critique of past journals. Based on the result, the young modulus and ultimate tensile strength of the epoxy grouts are decreased with increasing temperature. The increment of temperature causes the epoxy grouts to become weaker due to the changes in the polymer matrix structure of the epoxy grouts which lead to the failure at low load and shortens the life of the material. In addition, epoxy grouts are amorphous materials where the glass transition temperature determine the mechanical and physical properties of epoxy grouts. Therefore, the results of the study found that the epoxy grouts changed its mechanical properties from brittle to ductile when the temperature is at 72°C. From the comparison between samples immersed and not immersed in seawater, there is a decrease in Young’s modulus, ultimate tensile stress and strain due to the effect of seawater reaction. In conclusion, the increment in temperature and seawater adaptation factors affect the strength and durability of epoxy grouts.